Aktualisasi Kinerja Guru Tersertifikasi dalam Peningkatan Proses Pembelajaran pada MIN Tungkob Kabupaten Aceh Besar - Nurul Falah (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Certification is the process of awarding competence certificates in recognition of a person's ability to perform a job after passing a competency test. Teachers as a determinant of the success of the implementation of teaching and learning is required to produce high performance in carrying out duties and responsibilities to the fullest. This study actualizes the performance of certified teachers in teaching learning process in MIN Tungkob Aceh Besar. The formulation of the problem in this research; 1) How is the actualization of certified teacher performance in improving the learning process at MIN Tungkob Aceh Besar? 2) How is certified teacher planning in improving the learning process at MIN Tungkob Aceh Besar? 3) How is the implementation of certified teachers in improving the learning process in MIN Tungkob Aceh Besar? 4) How is the evaluation of certified teachers in improving the learning process at MIN Tungkob Aceh Besar? This research uses descriptive method with qualitative approach, data collection technique is done through observation, interview and documentation study. Research subjects were madrasah supervisors, madrasah heads and certification teachers. The results showed that: 1) Actualization of the performance of certified teachers in improving the learning process can be seen from the timeliness in carrying out the learning process, the accuracy of time come to school and going home on time. All discipline-certified teachers where if there are teachers who are unable to attend, they remain responsible for hours of learning in the like as with entrusted duty to the teacher picket; 2) Planning of certified teachers in improving the learning process can be seen from their preparation in making a good learning administration by preparing learning tools according to curriculum such as making syllabus, semester program, weekly program and RPP with the guidance of senior teachers and supervisors in teacher work group forum; 3) The implementation of certified teachers in improving the learning process undertaken is to provide early motivation, applying perceptions, using appropriate instructional media, managing classes, and methods used in the learning process varies, although of all these efforts have not all gone well. This is evident from the implementation that is still not maximized, so it seems only limited to the mere routine so that the learning process in the classroom running is not conducive and using a monotonous method; 4) Teachers carry out evaluation in all aspects of assessment ie cognitive, affective and psychomotor. The evaluation is conducted an on going basis, although there are still a small number of certification teachers who have not understood the problem analysis techniques so it is difficult to determine valid questions, all because the teacher has limited understanding of learning evaluation techniques.